Pelatihan Anak-anak TPA di Desa Durian Dalam Meningkatkan Ibadah Fi’liyah dan Qauliyah - Neneng Sulinah; Ramadhani Fajri; Subhi Nur Ishaki; Ulil Albab; Sulastri Sulastri (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The instilling of religious and moral values ​​in early childhood is not limited to intellectual aspects alone, but also includes familiarization with life in society and daily activities. Belief in a religious teaching that is considered effective for children and the younger generation occurs through religious teaching practices taken from the environment, TPA and society. The key parameter is how children as the nation's successors must learn and practice the spiritual worship they need and how this becomes their religious identity and character, such as in worship and being able to read the Koran well and correctly. The aim of the coaching carried out in this service is to increase awareness and transfer knowledge to provide insight to children at the TPA in Durian village, Padangmiri sub-district, Pesawaran district. The method used as an analytical tool in this research is a participatory research method between children and researchers which aims to encourage better living conditions. From this research it can be concluded that the TPA children in Durian Village after participating in community service are able to practice and apply the teachings of worship, especially when carrying out spiritual worship, namely performing ablution, praying and reading the Qoran.